Evolutionary conservation genetics - Höglund, Jacob, 1958- (Oxford biology., 2009)
Conservation genetics focuses on understanding the role of genetic variation for population persistence. This book is about the methods used to study genetic variation in endangered species and whether genetic variation matters in the extinction of species. - ;Conservation genetics focuses on understanding the role and requirement of genetic variation for population persistence. However, considerable debate now surrounds the role of genetic factors (as opposed to non-genetic factors such as habitat destruction etc.) in population extinction, and a comprehensive synthesis is now timely. Can ext.